2013
DOI: 10.1038/jcbfm.2013.83
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Whole-Brain White Matter Identifies Altered Water Mobility in the Pathogenesis of High-Altitude Headache

Abstract: Elevated brain water is a common finding in individuals with severe forms of altitude illness. However, the location, nature, and a causative link between brain edema and symptoms of acute mountain sickness such as headache remains unknown. We examined indices of brain white matter water mobility in 13 participants after 2 and 10 hours in normoxia (21% O 2 ) and hypoxia (12% O 2 ) using magnetic resonance imaging. Using a whole-brain analysis (tract-based spatial statistics (TBSS)), mean diffusivity was reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 30 publications
4
25
0
Order By: Relevance
“…In the present study, iron deposits might have resulted in a significant T2 decrease of the Dg region in the 14-day HH group. It is clear from the current study that cytotoxic edema occurs in hippocampal subfields in response to prolonged HH, which is in accordance to earlier studies which showed a decrease in ADC values in the cerebral GM region (Hunt et al, 2013;Lawley et al, 2013).…”
Section: Hh-induced Structural Changes In Hippocampussupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, iron deposits might have resulted in a significant T2 decrease of the Dg region in the 14-day HH group. It is clear from the current study that cytotoxic edema occurs in hippocampal subfields in response to prolonged HH, which is in accordance to earlier studies which showed a decrease in ADC values in the cerebral GM region (Hunt et al, 2013;Lawley et al, 2013).…”
Section: Hh-induced Structural Changes In Hippocampussupporting
confidence: 94%
“…A decrease in ADC may indicate redistribution of water from the extracellular to the intracellular compartment, which is being hypothesized as cytotoxic edema in the cerebral GM due to hypoxia (Pulsinelli, 1985). This decrease in ADC values was in agreement with earlier studies performed on mountaineers (Hunt et al, 2013;Lawley et al, 2013). Histopathology of 7-day HH rats revealed a change in CA1 architecture.…”
Section: Hh-induced Structural Changes In Hippocampussupporting
confidence: 85%
“…Furthermore, 24 hours before and during each visit, participants consumed a standardized diet. 12 Each visit consisted of a 10-hour exposure to normobaric normoxia (21% O 2 ) or normobaric hypoxia (12% O 2 ) in a temperature (23 C) and humidity (40%) controlled environmental chamber. Participants were assigned to each exposure in a randomized order (www.randomisation.com, by J.S.L.)…”
Section: Experimental Protocolmentioning
confidence: 99%
“…[12][13][14] Furthermore, lumbar pressure is elevated in individuals with suspected high-altitude cerebral edema, 15 but not in individuals with AMS after 18 hours in normobaric hypoxia. 9 Thus, the precise role brain volume and ICP play in causing symptoms of AMS is still debated.…”
mentioning
confidence: 96%
“…2,7 Although the 'tight-fit' hypothesis suggests that increased brain volume and subsequent enhanced intracranial pressure may underlie AMS symptoms, 7 the link between changes in brain volumes, signs of cerebral edema, and symptoms of AMS typically developing over the first 6 to 12 hours of hypoxic exposure remains controversial. 3,4,[8][9][10] Some reports suggest that performing physical activity during the first hours of hypoxic exposure may accentuate symptoms of AMS. [11][12][13] Only one recent study compared the effects of hypoxic exposure for 8 hours associated or not with physical exercise (3 times 30 minutes of moderate intensity exercise) on brain volume and cerebral edema.…”
Section: Introductionmentioning
confidence: 99%